Trade and tariff act of 1984 : trade policy in the Reagan administration - Lande, Stephen L. (Lexington Books LexingtonUS, 1986)
Describes the origins , provisions, and significance of the Trade and Tariff Act (TTA). Discusses the historical development of US trade policy focusing on the creation of a liberal system based on American interests. Outlines the changes to this system describing the negotiating objectives and authority that the TTA provides for the executive branch; the trade remedy statutes which help domestic companies restrict unfair competition; and the ammendments to US antisubsidy and antidumping statutes. Outlines measures in the TTA aimed at specific products and sectors, the most important being the steel Import Stabilization Act of 1984. Discusses prospects for US trade policy in the near term.